2021
DOI: 10.1186/s12966-021-01166-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leisure time physical activity and sedentary behaviour on the health of workers with different occupational physical activity demands: a systematic review

Abstract: Background Although it is generally accepted that physical activity reduces the risk for chronic non-communicable disease and mortality, accumulating evidence suggests that occupational physical activity (OPA) may not confer the same health benefits as leisure time physical activity (LTPA). It is also unclear if workers in high OPA jobs benefit from LTPA the same way as those in sedentary jobs. Our objective was to determine whether LTPA and leisure time sedentary behaviour (LTSB) confer the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 95 publications
(59 reference statements)
5
51
4
1
Order By: Relevance
“…For instance, we also observed in our meta-analysis that self-reported workplace sitting of cross-sectional studies be positively associated with LBP in non-tradespeople but not in tradespeople, albeit in a limited number of studies. Some proponents of the “physical activity paradox” assert that sitting could be of health benefit in individuals who regularly engage in high occupational physical activity as sitting may allow some form of rest and recovery [ 40 , 41 ]. These indications in our review are, however, inconclusive and warrant further investigations in diverse occupational settings to ascertain these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, we also observed in our meta-analysis that self-reported workplace sitting of cross-sectional studies be positively associated with LBP in non-tradespeople but not in tradespeople, albeit in a limited number of studies. Some proponents of the “physical activity paradox” assert that sitting could be of health benefit in individuals who regularly engage in high occupational physical activity as sitting may allow some form of rest and recovery [ 40 , 41 ]. These indications in our review are, however, inconclusive and warrant further investigations in diverse occupational settings to ascertain these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SB associations may also reflect plausible biomechanical or biological pathways explaining MSP conditions in those exposed to prolonged static sitting postures [ 36 38 ]. Paradoxically, however, in occupational groups such as tradespeople who engage in more labour-intensive manual work, SB may be a protective behaviour against MSP conditions and other chronic diseases [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies should also utilize the gold standard techniques to measure ST (i.e., a thigh-worn monitor) and HRV (i.e., ECG with guideline-based processing and accounting for respiration rate). Other sources of potential heterogeneity that we were unable to disentangle may also be important future research directions such as preexisting CVD, domains and patterns of ST, and diurnal vs. nocturnal HRV measurement [67][68][69][70]. Finally, given that the COVID-19 pandemic has negatively affected lifestyle behaviors and mental health [71], future studies should investigate the role of the pandemic in the associations between ST and HRV.…”
Section: Implications and Future Directionsmentioning
confidence: 98%
“…Some studies show that both physical activities do not interact and work independently (Holtermann et al 2021;Krause et al 2017). Other studies have shown that off-job physical activity protects blue-collar workers' physical health (Leino-Arjas et al 2004;Quinn et al 2021) or particularly white-collars' level of burnout (Bernaards et al 2006;Prince et al 2021). To the best of our knowledge, no previous study has investigated the impact of the combination of physical activity on and off the job on burnout.…”
Section: The Combination Of Physical Activities On and Off The Jobmentioning
confidence: 99%
“…These findings suggest that the simultaneous enactment of different physical activities alters their potential unique effects (cf. Prince et al 2021). Therefore, researchers should not restrict themselves to one domain-specific physical activity when studying possible positive effects following physical activity.…”
Section: Tablementioning
confidence: 99%